Compulsory and Voluntary Biometrics: Content and Distinction in Russian Law - Z. O. Mitianov (Теоретическая и прикладная юриспруденция)
The article examines the peculiarities of separation and differentiation of two areas included in the sphere of biometric personal data processing in Russia: compulsory and voluntary biometrics. The definitions of the concepts of these areas are formulated, the peculiarities of their content are considered. Justification of their differentiation, main criteria and specifics of such differentiation are given. The problems of voluntary biometrics in the context of exceptional cases of compulsory processing of biometric personal data are highlighted. The balance of private and public interests in each of the areas is studied. The conclusions are drawn about the formation of the scope of voluntary biometrics and its differentiation from compulsory biometrics due to the legislative novelties at the end of 2022; the essential difference between compulsory biometrics and voluntary biometrics; the existence of special criteria for differentiating between voluntary and compulsory biometrics; the need to focus lawmaking efforts on voluntary biometrics due to its dynamism and closeness to everyday life.